Unilateral Stimulation of Subthalamic Nucleus Does Not Affect Inhibitory Control - Mancini, Christian; Modugno, Nicola; Santilli, Marco; Pavone, Luigi; Grillea, Giovanni; Morace, Roberta; Mirabella, Giovanni (Frontiers in Neurology, 2019)
Despite the relevance of inhibitory control in shaping our behavior its neural substrates are still hotly debated. In this regard, it has been suggested that inhibitory control relies upon a right-lateralized network which involves the right subthalamic nucleus (STN). To assess the role of STN, we took advantage of a relatively rare model, i.e. advanced Parkinson’s patients who received unilateral deep-brain stimulation (DBS) of the STN either of the left (n=10) or of the right (n=10) hemisphere. We gave them a countermanding reaching task, and we compared patients’ performance in two experimental conditions, DBS-ON and DBS-OFF. In addition, we also tested 22 age-matched healthy participants. As expected, we found that inhibitory control is impaired in Parkinson’s patients with respect to healthy participants. However, neither reactive nor proactive inhibition is improved when either the right or the left DBS is active. We interpreted these findings in light of the fact that previous studies, exploiting exactly the same task, have shown that only bilateral STN DBS restores a near-normal inhibitory control. Thus, although null results have to be interpreted with caution, our current findings confirm that the right STN does not play a key role in suppressing pending actions. However, on the ground of previous studies, it is very likely that this subcortical structure is part of the brain network subserving inhibition but to implement this executive function both subthalamic nuclei must be simultaneously active. Our findings are of significance to other researchers studying the effects of STN DBS on key executive functions such as impulsivity and inhibition and they are also of clinical relevance for determining the therapeutic benefits of STN DBS as they suggest that, at least as far as inhibitory control is concerned, it is better to implant DBS bilaterally than unilaterally